Deliberation and Collective Identity. Commisive, Directive and Expressive Uses of Argument (2020)
The prevailing conception of argumentation continues to favor the representational dimension of language and, therefore, ignores or underestimates the compromising, directive, or expressive functions of argumentation. This paper examines the uses of argumentation in the public arena, focusing on deliberation and negotiation in particular, to bring to light and assert the importance of the non-persuasive roles of argumentation, including social identity construction and modeling.